Ernest Irwandi EVALUASI PENDEKATAN PARTISIPATORI DALAM SENI, STUDI MURAL KOMUNITAS DI KAMPUNG KOTA - Ernest Irwandi; Setiawan Sabana; Andryanto Rikrik Kusmara (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Mural art does not only function as decoration but it is an art activity that impact social life. Decorating villageswith murals has become an art movement across Java. Creation of mural in these villages involves manystakeholders (government, universities, students, artists), which can be considered as participatory art, thatemphasize on collaboration and shared experiences. In participatory art, artists’ and facilitator role is to encouragecommunity creativity. This research focuses on art community murals using participatory action researchapproach. This research aim to analyze collaborative art creation models, and examine how art canempower a community.